High-Impact Weather Events over the SAARC Region - Ray, Kamaljit; Mohapatra, M.; Bandyopadhyay, B.K.; Rathore, L.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is a compilation of papers contributed by researchers and scientists from SAARC nations and deals with high-impact weather conditions, their prediction and potential consequences for populations in the SAARC region. There have been a number of recent advances in our understanding and prediction of cyclones, severe thunderstorms, squalls, heat and cold waves, droughts and heavy rainfall, based on the latest observational data and NWP modeling platform. The SAARC region is vulnerable to high-impact weather events because of geographical features like high mountains, plateaus and vast oceans. As our climate continues to change over the coming years, the likelihood of extreme and potentially high-impact weather and climate events will be at its highest when natural and anthropogenic effects combine. All chapters were written by leading experts in their respective research and operational fields. The book reviews the latest research, future needs, forecasting skills and societal impacts of extreme weather events and offers high-quality reference material for weather forecasters, disaster managers and researchers.
Preface -- About the Editors -- Study of Severe Thunderstorms over Bangladesh and Its Surrounding Areas during Pre-monsoon Season of 2013 Using WRF-ARW Model -- Assimilation of Doppler Weather Radar Data through Rapid Intermittent Cyclic (RIC) for Simulation of Squall Line Event over India and adjoining Bangladesh -- Impact of Data Assimilation in Simulation of Thunderstorm Event over Bangladesh Using WRF Model -- Numerical Simulation of a Hailstorm Event over Delhi, India on 28 March 2013 -- Simulation of Mesoscale Convective Systems Associated with Squalls Using 3DVAR Data Assimilation over Bangladesh -- Simulation of Severe Convective Weather Events over Southern India Using WRF Model -- Early Warning Services for Management of Cyclones over North Indian Ocean: Current Status and Future Scope -- Development of NWP-based Cyclone Prediction System for Improving Cyclone Forecast Service in the Country -- Interannual and Interdecadal Variations in Tropical Cyclone Activity over the Arabian Sea and the Impacts over Pakistan -- Impact of Cloud Microphysics and Cumulus Parameterisation on Mesoscale Simulation of TC Sidr over the Bay of Bengal Using WRF Model -- Eddy Angular Momentum Fluxes in Relation with Intensity Changes of Tropical Cyclones Jal (2010) and Thane (2011) in North Indian Ocean -- Impact of Initial and Boundary Conditions on Mesoscale Simulation of Bay of Bengal Cyclones Using WRF-ARW Model -- Performance of Global Forecast System for the Prediction of Intensity and Track of Very Severe Cyclonic Storm ‘Phailin’ over North Indian Ocean -- Observational Analysis of Heavy Rainfall during Southwest Monsoon over India -- Long Term Trends in the Extreme Rainfall Events over India -- Diagnostic Study of Heavy Rainfall Events in Monsoon Season over Northern Part of Bangladesh Using NWP Technique -- Analysis of Increasing Heavy Rainfall Activity over Western India, Particularly Gujarat State, in the Past Decade -- Simulation of Heavy Rainfall Event over Gujarat during September 2013 -- Simulation of Rainfall over Uttarakhand, India, in June Using WRF-ARW Model and Impact of AIRS Profiles -- Incessant Rainfall Event of June 2013 in Uttarakhand, India: Observational Perspectives -- Convergence of Synoptic and Dynamical Conditions Responsible for Exceptionally Heavy Rainfall over Uttarakhand, India -- Changes in Rainfall Concentration over India during 1871-2011 -- Identifying the Changes in Rainfall Pattern and Heavy Rainfall Events during 1871-2010 over Cherrapunji -- Agricultural Drought Assessment: Operational Approaches in India with Special Emphasis on 2012 -- Trends in Extreme Temperature Events over India during 1969-2012 -- Analysis of Extreme High Temperature Conditions over Uttar Pradesh, India -- Use of Remote Sensing Data for Drought Assessment: A Case Study for Bihar State of India during Kharif, 2013 -- Index.
Keywords: Atmospheric sciences; Meteorology; Climatology; Climate change; Natural disasters; Atmospheric Sciences; Meteorology; Climatology; Climate Change/Climate Change Impacts; Natural Hazards